The Influence of Return On Equity, Net Profit Margin, Debt To Equity Ratio, and Dividend Payout Ratio On Stock Returns In Coal Sub Sector Companies Listed On The IDX 2018-2022 - Cindy Siti Karmilah; Esi Fitriani Komara (Dinasti Publisher, 2024)
Happen fluctuations in stock returns in coal sub-sector companies for the 2018-2022 period. This research aims to determine the effect of return on equity, net profit margin, debt to equity ratio, and dividend payout ratio on stock returns in coal sub-sector companies listed on the IDX for the 2018-2022 period. The method used in this research is quantitative. The type of data used is secondary data with a population of 31 coal companies using a purposive sampling method and 19 companies used as samples. The data analysis technique used is panel data regression. The research results show that ROE, NPM, DER, and DPR influence stock returns.